PENINGKATAN PEMAHAMAN MANAJEMEN LAKTASI DAN PEMANFAATAN APLIKASI SIMOMI UNTUK MENDUKUNG GERAKAN PRO-ASI DI DESA JATIKERTO KABUPATEN MALANG INDONESIA - Hayatin, Nur; Alifatin, Aini; Andhini, Thathit Manon; Kurniawati, Dini (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2019)
At present, mothers' awareness of the importance of lactation has begun to develop. This is an effect of inseparable from the role of government and related associations who always provide campaigns and counseling on the importance of breastfeeding to maximize the growth and development of infants. Lactation management is an effort to support the success of lactation starting during pregnancy, childbirth, and breastfeeding. Mothers learn about lactation management from direct counseling or learning independently from articles and books. In Malang district, although the percentage of breastfeeding mothers is quite high, the local government still encourages the provision of breast milk (breast milk) specifically. The Malang Regency Government will issue an official regulation in the form of a PerBup (Regents of the Regent) regarding exclusive breastfeeding. PERBUP is made as a quick response to the movement of breastfeeding to infants under two years of age. This movement is trying to be supported by the proposing team through an extension activity and training on lactation. The proposed service activities aim to provide counseling or socialization and training in lactation management. Through this program training, activities will be carried out on application use by collaborating with partners from PKK Extension of ASI Extension staff in Jatikerto Village, Kromengan sub-district under the auspices of the Office of Women's Empowerment and Child Protection (KP3A) Malang Regency. We hope to be able to participate in supporting government programs in the awareness movement of exclusive breastfeeding for the community to optimally fulfill nutrition and infant development.